The Second Phase Extended Mission Orbit Design for the Korea Pathfinder Lunar Orbiter - Young-Joo Song; Seungbum Hong; Jun Bang; Jonghee Bae; Moon-Jin Jeon (IEEE Access)
The Korea Pathfinder Lunar Orbiter (KPLO), also known as Danuri, has completed its primary mission and is now in the first phase of its extended mission. Given the current overall programmatic status, particularly the spacecraft’s health and remaining fuel, executing the second phase of the extended mission appears viable. This study presents the design and evaluation of the second phase of the Extended Mission Orbit (EMO) for KPLO, focusing on the practical considerations and rationale behind designing the additional extended mission. The process began with a preference survey conducted among the science Principal Investigators (PIs) of the onboard payloads to maximize scientific output and solidify the extended mission. Following this, real-world operational constraints were considered to refine and finalize the candidate EMOs. The study introduces two viable candidates for the second phase of EMO scenarios for KPLO, along with details of associated operational timelines, maneuvers, and orbital characteristics. The feasibility of both candidate orbits has been confirmed from the perspective of flight dynamics. However, the final decision on which EMO scenario to implement remains undecided. The ultimate selection will greatly depend on the operational results up to 2025. Regardless of which EMO option is ultimately chosen, ongoing analyses based on real-time flight data will allow for adjustments and refinements to the EMO plans, ensuring compliance with planetary protection requirements and optimizing the mission’s success. This study comprehensively addresses all critical aspects of EMO design by combining real-world operational constraints with scientific objectives, providing practical insights for future lunar exploration missions.